A passive compensator for imbalances in current sharing of parallel‐siC MOSFETs based on planar transformer - Mahdi Delzendeh Sarfejo; Hesamodin Allahyari; Hamid Bahrami; Ahmad Afifi; Mohammad Ali Latif Zadeh; Ehya Yavari; Mahdi Ghavidel Jalise (IET Power Electronics, 2021)
Abstract SiCMOSFETs are widely employed in power converters due to their high switching speed and low switching loss. However, their low current rating due to the limited active area restricts their high power applications. To apply SiC MOSFETs in high power applications, providing parallel connection is an inevitable choice. To tackle the challenge of imbalanced current sharing problem between parallel SiC MOSFETs, a new passive compensator based on planar transformer (PT) is proposed here. Compared with the conventional transformer compensators, parasitic elements are adjustable and predictable in PT compensators, which is especially important for mass production aims. After explaining the concept of the physical operation of the PT compensator, the whole parasitic elements of the PT compensator are formulated. Based on estimated parasitic elements and using the finite element method (FEM), an optimum PT structure is extracted for imbalances in current sharing of parallel SiC MOSFETs. Afterward, the PT design is discussed in detail and then, a boost converter is constructed. Finally, the experimental results are presented to verify the reliability, accuracy, and effectiveness of the theoretical results.